Children in the Trap of Habitus: Power and Domination in Inem and Sunat by Pramoedya Ananta Toer - Indriyani, Jiphie Gilia; Adzhani, Shabrina An; Savitri, Ima Dyah; Atiqurrahman, Moh (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study analyses the short stories Inem and Sunat in the collection Cerita dari Blora by Pramoedya Ananta Toer using Pierre Bourdieu's theory. Both short stories represent social realism through the experiences of children trapped in oppressive social structures. Using the habitus approach, this research reveals how cultural values and social norms shape the life experiences of the main characters in both stories. Analysis of social, economic and cultural capital shows that the children in these short stories have limited access to freedom and social mobility. In Inem, the female protagonist is a victim of the patriarchal system and early marriage, while in Circumcision, the boy character experiences social pressure in undergoing cultural rituals that he does not fully understand. This research shows that social inequality in society is reproduced through a value system that is passed down through generations, limiting children's roles and life choices. Using Bourdieu's perspective, this research provides new insights into the position of children in social realism literature and how the social system shapes their experiences.